2011
DOI: 10.1159/000329046
|View full text |Cite
|
Sign up to set email alerts
|

Normal Tempo of Bone Formation in Turner Syndrome despite Signs of Accelerated Bone Resorption

Abstract: Aims: To evaluate area bone mineral density (aBMD) and volumetric BMD (vBMD) by dual-energy X-ray absorptiometry, and relations to bone markers and hormones in adolescent women with Turner syndrome (TS). Methods: Cross-sectional study in TS patients (n = 37, 16.7 ± 3.4 years) and control group (n = 49), assessed by dual-energy X-ray absorptiometry, bone markers and hormones. TS patients were divided into a young group receiving (‘ongoing’) GH (n = 15) and an older group previously receiving (‘previous’) GH (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…The positive effects of GH therapy on bone have been shown in several studies (Cleemann et al, ; Sas et al, ). The former study showed improvement in BMD using variable dose regimen of GH.…”
Section: Endocrine Issuesmentioning
confidence: 91%
See 1 more Smart Citation
“…The positive effects of GH therapy on bone have been shown in several studies (Cleemann et al, ; Sas et al, ). The former study showed improvement in BMD using variable dose regimen of GH.…”
Section: Endocrine Issuesmentioning
confidence: 91%
“…The Guidelines (Gravholt, Andersen, et al, , section 2.5) recommend confirming ovarian dysfunction, and starting estrogen replacement between 11 and 12 years of age in order to promote normal growth and psychosocial development. Low doses of estradiol are initiated and titrated to promote secondary sexual characteristics and uterine growth without early closure of the growth plates, ensure a normal tempo of bone mineralization (Cleemann et al, ), normalize cognitive maturation (Ross, Roeltgen, Feuillan, Kushner, & Cutler Jr., ; Ross, Roeltgen, Feuillan, Kushner, & Cutler Jr., ), body composition (Cleemann et al, ), reduce lipids (Gravholt, Naeraa, et al, ) and liver enzymes (Koulouri, Ostberg, & Conway, ) and reduce cardiovascular risk in the long term (Gravholt, Naeraa, et al, ; Ostberg et al, ). Transdermal estradiol is the preferred method for estrogen administration (Gravholt, Andersen, et al, , section 6.1; Klein et al, ), but oral estradiol can also be used.…”
Section: Endocrine Issuesmentioning
confidence: 99%
“…Young TS patients undergoing pubertal induction and still receiving GH had lower z-score BMD than older TS patients receiving HRT, where a near-normalised BMD was achieved. Patients previously receiving GH showed signs of increased bone resorption (103).…”
Section: Bonementioning
confidence: 99%
“…In a former cross-sectional study, we found a normal tempo of bone formation in a large group of girls and adolescent with TS compared to healthy controls despite signs of accelerated bone resorption (19). In the present prospective study, we hypothesized that high-dose oral 17B-estradiol in young women with TS would have beneficial effects on BMD and body composition and correct the imbalance between bone formation and bone resorption.…”
Section: Dosage Of Estradiol Bone and Body Composition In Turner Synmentioning
confidence: 70%
“…Increased LBM, and thus probably muscle strength, is also likely to have additional positive roles in relation to the frequent occurrence of type 2 diabetes, hypertension, impaired postural balance (32) and obesity (33). A few studies have looked at markers of bone metabolism to account for differences in the bone phenotype in TS (18,19) and found markers of bone formation and levels of vitamin D to be similar in girls with TS compared to healthy girls. However, markers of bone resorption were elevated in TS.…”
Section: Discussionmentioning
confidence: 99%